n+9=4v-6

Simple and best practice solution for n+9=4v-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n+9=4v-6 equation:


Simplifying
n + 9 = 4v + -6

Reorder the terms:
9 + n = 4v + -6

Reorder the terms:
9 + n = -6 + 4v

Solving
9 + n = -6 + 4v

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + n = -6 + -9 + 4v

Combine like terms: 9 + -9 = 0
0 + n = -6 + -9 + 4v
n = -6 + -9 + 4v

Combine like terms: -6 + -9 = -15
n = -15 + 4v

Simplifying
n = -15 + 4v

See similar equations:

| 8y=3x-12 | | 2(1+8x)=4(4x+8) | | ax+y=bx+K | | -6(4x-6)=-18-6x | | (3i+8)(6i-7)= | | 4(x+5)-2x+2=3(2x-4)+x+9 | | x+90+70=180 | | -3(4v+8)=-18-6v | | H(t)=-16t^2+342+1000 | | 4/2x-2916=1/9 | | x^2+6x+12=2x-1 | | 30=-w+247 | | -7b+28=-8(5+3b) | | 4(32-2b)=144 | | 242-u=133 | | 1+7x=4x+16 | | 3(2x+5)=(3x+3) | | 5m+m-2m=20 | | 12n=7 | | 7p+2p+2p-p-2p=16 | | 16b-9b-b=18 | | y=-5t^2+20t+60 | | √2/2x-54=1/3 | | ln0.9/ln2= | | 17c+2c+2c-12c=9 | | 2t-2t+4t+t-3t=20 | | 7(2x+7)= | | 3p-2p+p= | | (a-2)/2=-1 | | 4(c-5)=12 | | 21=-3(1-2x)-6(x-5) | | 6r-r=20 |

Equations solver categories